CONTRACTUAL MONITORING IN PUBLIC-PRIVATE PARTNERSHIPS: PERFORMANCE INDICATORS AS AN EFFICIENCY TOOL - de Sousa Filho, Demerval Nunes (Seven Editora, 2026)
Public-Private Partnerships (PPPs) have consolidated themselves as a strategic instrument for infrastructure development and the provision of public services. However, the success of such long-term contractual arrangements does not lie solely in the quality of their initial structuring, but rather in the effectiveness of their ongoing management. This paper examines the critical importance of monitoring PPP contracts, with particular emphasis on the role of performance indicators as essential mechanisms for assessing compliance with contractual obligations and ensuring the quality of services delivered to the population. It argues that such indicators operate as signals of non-compliance, enabling risk management within a framework analogous to the Heinrich Pyramid. Furthermore, the study explores the superiority of performance-linked deduction mechanisms in variable remuneration, as opposed to traditional sanction-based systems, demonstrating their greater efficiency, celerity, and lower propensity for judicialization. Finally, the paper addresses the essential material limits applicable to such deductions, arguing that they should be restricted to the project’s profitability margin, while preserving operational costs and debt servicing, in order to ensure economic-financial sustainability and the continuity of public service provision.